2013
DOI: 10.1523/jneurosci.3521-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Precise Neural Stimulation in the Retina Using Focused Ultrasound

Abstract: Focused ultrasound is a promising noninvasive technology for neural stimulation. Here we use the isolated salamander retina to characterize the effect of ultrasound on an intact neural circuit and compared these effects with those of visual stimulation of the same retinal ganglion cells. Ultrasound stimuli at an acoustic frequency of 43 MHz and a focal spot diameter of 90 m delivered from a piezoelectric transducer evoked stable responses with a temporal precision equal to strong visual responses but with shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
160
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(173 citation statements)
references
References 23 publications
11
160
2
Order By: Relevance
“…The diameter of the stimulated volume is typically several millimeters for applications through the human skull, 18 and can attain approximately 100 μm in soft-tissue applications. 39 FUS can excite or inhibit cellular activity, depending on specific stimulation parameters. 47 FUS can cause a transient increase in firing rates in motor cortex and in the retina with short latency, 39,55 and thus has a direct capability to influence cellular discharge.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the stimulated volume is typically several millimeters for applications through the human skull, 18 and can attain approximately 100 μm in soft-tissue applications. 39 FUS can excite or inhibit cellular activity, depending on specific stimulation parameters. 47 FUS can cause a transient increase in firing rates in motor cortex and in the retina with short latency, 39,55 and thus has a direct capability to influence cellular discharge.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
“…39 FUS can excite or inhibit cellular activity, depending on specific stimulation parameters. 47 FUS can cause a transient increase in firing rates in motor cortex and in the retina with short latency, 39,55 and thus has a direct capability to influence cellular discharge. It has been hypothesized that these effects are mediated by ion channels that can detect changes in membrane stretch following a propagating pressure wave.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
“…Although research on the effects of ultrasound on excitable tissue dates back to the 1920s [4], several recent results have revived interest in this phenomenon. Reversible changes in action potential frequency in response to low-intensity ultrasound (on the order of 0.1–10 W/cm 2 ) have been observed in vitro [5], [6] and in vivo [7], [8], [9], [10], [11]. In addition, transducer arrays that transmit ultrasound through the human skull have been implemented in high-intensity focused ultrasound surgery [12], [13], [14], [15], and it has been proposed that this technology could be adapted to deliver low-intensity ultrasound for the treatment of neurological disorders [5], [10].…”
Section: Introductionmentioning
confidence: 98%
“…Using this modality, a series of studies have demonstrated ultrasound-mediated stimulation of neural activity sufficient to elicit action potentials and synaptic transmission in vitro (Kraiche et al, 2008, Tyler et al, 2008, Menz et al, 2013), and in vivo in mice (motor cortex: Tufail et al, 2010, King et al, 2013; hippocampus: Tufail et al, 2010), without significant elevation in brain temperature (< 0.01°C). Average response latencies (~50–150 ms), while better than with the magnetothermal approaches, remain considerably slower than with typical optogenetic experiments (< 5 ms).…”
Section: Introductionmentioning
confidence: 99%